Evaluation of the Nutritive Values of Carica Papaya Fruit peels as A Potential Ingredient in Livestock Nutrition - Adeyinka Oye Akintunde; Pokpah Kolu; Ibukunoluwa Adenike Akintunde; Samuel Adegoke Adewole; Olufunso Emmanuel Akinboye; Osagie John Afodu; Lois Chidinma Ndubuisi-Ogbonna; Bolatito Adenike Shobo (ANIMAL PRODUCTION, 2022)
The nutritive values of the peels of ripe and unripe fruits of Carica papaya were assessed for their potential in livestock production. Proximate and phytochemical analyses, as well as vitamins and mineral contents of the ingredients, were determined. Data were subjected to a t-test for statistical analysis. The crude protein (CP) of ripe and unripe Carica papaya peels were 3.50% and 10.30%. The ripe Carica papaya peels had 26.20%, 3.05%, 15.03%, 3.71%, 52.22%, 2.44%, and 1,060.09Kcal/Kg of crude fiber, crude fat, ash content, moisture, carbohydrate, fatty acid, and energy respectively while the unripe Carica papaya peels contained 27.10%, 22.30%, 13.30%, 4.15%, 27.00%, 17.84% and 1,459.20Kcal/Kg of crude fiber, crude fat, ash content, carbohydrate, fatty acid, and energy respectively. The ripe Carica papaya peels had significantly higher (p<0.05) values for calcium (0.39%), potassium (0.40%) and iron (570mg/Kg). The ripe Carica papaya peels had significantly higher (p<0.05) values of saponin (9.69mg/100g) while the unripe peels had significantly higher values (p<0.05) for alkaloid (6.44mg/100g), hydrogen cyanide (0.57mg/100g) and tannin (86.90mg/100g. Ripe Carica papaya peels having significantly higher (p<0.05) values for vitamin B1 (1.67mg/100g) and vitamin B6 (1.80mg/100g) while the unripe Carica papaya peels had significantly higher (p<0.05) values for vitamin A (3360IU/Kg), vitamins B2 (0.45mg/100g), B3 (3.25mg/100g), B12 (0.92mg/100g) and C (9.78mg/100g). It is concluded that these products offer a good source of basic vitamins and minerals and hold potential for therapeutic use in livestock nutrition. Therefore, the inclusion of these ingredients should be encouraged in livestock production, especially in the industry of monogastric animals.